2020
DOI: 10.1016/j.apor.2020.102127
|View full text |Cite
|
Sign up to set email alerts
|

Wave flume testing of an oscillating-body wave energy converter with a tuned inerter

Abstract: In this study, the effectiveness of an oscillating-body WEC with a tuned inerter (TI) proposed by the authors is shown through wave flume testing. The TI mechanism consisting of a tuning spring, a rotational inertial mass, and a viscous damping component is able to increase energy absorption capability by taking advantage of the resonance effect of the rotational mass. This mechanism has been recently introduced for civil structures subjected to external loadings such as earthquakes and winds to decay vibratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In addition, algorithms to control the stiffness and damping of the PTO system with regard to the change of the sea state are desired. Furthermore, experimental investigation [39] to assess the feasibility of the device under real sea condition is required. This includes the consideration of locking the PTO system in survival mode and understanding the buoy response to highly non-linear extreme waves.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, algorithms to control the stiffness and damping of the PTO system with regard to the change of the sea state are desired. Furthermore, experimental investigation [39] to assess the feasibility of the device under real sea condition is required. This includes the consideration of locking the PTO system in survival mode and understanding the buoy response to highly non-linear extreme waves.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the power generation performance of a conventional singlebody point absorber WEC, which has one floating buoy, the authors employed a tuned inerter mechanism [14,15]. Originally, the tuned inerter mechanism was proposed by [16] as a structural control device to absorb vibration energy effectively from vibrating civil structures such as buildings induced by seismic disturbances and to mitigate damage.…”
Section: Introductionmentioning
confidence: 99%
“…The authors employed a generator or a motor as the linear damping element in the tuned inerter mechanism and showed that the mechanism enhances the ability to extract energy from vibrating structures at a low frequency of less than 10 Hz [18,19]. In addition, the authors proposed a single-body point absorber WEC with a tuned inerter and the efficacy of the present device was shown through numerical simulation studies [14] and wave flume testing using a small-scale prototype model [15]. However, generally, the single-body point absorber WEC needs to be connected directly to the ocean floor.…”
Section: Introductionmentioning
confidence: 99%
“…A self-sensing harvester, which measures temperature [3], displacement [4], and body motions [5] without the use of specific sensors and batteries, has also been proposed for advanced applications. Transducers for vibration energy harvesting include tuned mass dampers [6,7], magnetorheological elastomers [8], electromagnetic devices [9,10], electrets [11,12], magnetostrictive elements [13][14][15], and piezoelectric elements [16]. Piezoelectric transducers convert mechanical energy into electrical energy and vice versa as direct and inverse piezoelectric effects [17,18].…”
Section: Introductionmentioning
confidence: 99%